Chloride – induced delayed ettringite formation in Portland cement mortars. (18th July 2022) - Ekolu, Stephen; Solomon, Fitsum; Rakgosi, Gift
Highlights: DEF is delayed ettringite formation, CLIDEF is chloride – induced DEF. A new phenomenon CLIDEF is reported for the first time. CLIDEF is a function of chloride concentration of the storage solution. External chloride ingress induces pessimum expansion effect of CLIDEF. Peak CLIDEF occurs at 0.25 to 1.0 M NaCl concentration of storage solution. High chloride concentrations of storage solution mitigate CLIDEF expansion. Abstract: The present paper reports an obscure new phenomenon herein referred to as chloride – induced delayed ettringite formation (CLIDEF). In the study, mortar mixtures of proportions 1:2.25:0.47 cement to sand to water, were used to prepare 25 × 25 × 285 mm prisms. Incorporated into Portland cement CEM I 42.5R were varied sulphate levels of 2%, 3%, 4%, 5%, 7% and 8% total SO3 content. The prisms were cast and heat – cured at 95 °C then stored in chloride solutions of varied concentrations comprising 0, 0.25, 0.50, 0.75, 1.00, 1.50, 2.00, 3.0 M NaCl. Expansion values of the prisms were monitored for ages of up to 180 weeks. It was found that pessimum expansion occurred at 0.25 to 1.0 M NaCl concentrations. Cementitious systems that were non – expansive under storage in water became expansive upon storage in NaCl solutions of the optimum concentration range 0.25 to 1.0 M NaCl, giving rise to CLIDEF.